The warm sigh of Venus: reading of introductoy ekphrasis of De rerum natura of Lucretius (Argos, 2025)
The Venus' invocation that starts the book of Lucretius, De Rerum Natura, constitutes a poetic procedure of multiple sincretisms. In this paper we shall analyse the prooemiun through the resource of the description of artistic objects, called ekphrasis, and we will try to study its organisation, its lexical connotations and its epic-didactic function, at the beginning of the poem. We believe that this resource is important for the poem's interpretation since it is related to the literary and artistic world. This is a retoric procedure that legitimates the insertion of the epicurean conceptions of the human being and the world in the philosophical Latin context.
Keywords: Lucretius; ekphrasis; Venus; invocation; epicurean